Essential public manager - Pollitt, Christopher (Maidenhead, 2003)
The book provides a vigorous overview of such crucial topics as the differences and similarities between public and private sector management, the nature of the 'New Public Management', the development of networks and partnerships, the impacts of politics and citizen participation on public administration.
Keywords: Public Administration